2011
DOI: 10.1080/07315724.2011.10719969
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Polyunsaturated Fatty Acids Promote Paclitaxel Cytotoxicity via Inhibition of the MDR1 Gene in the Human Colon Cancer Caco-2 Cell Line

Abstract: Our results suggest that inhibition of the multidrug resistance MDR1/P-gp is one mechanism through which dietary polyunsaturated fatty acids exert a synergetic effect on the response of tumor cells to anticancer drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 54 publications
1
33
0
4
Order By: Relevance
“…A similar effect was produced by DHA and EPA in the Pgp-overexpressing Caco-2 cells treated with paclitaxel [59]. DHA and EPA fully restored both the direct cytotoxicity and the “indirect” pro-immunogenic toxicity of doxorubicin, i.e.…”
Section: Discussionmentioning
confidence: 72%
“…A similar effect was produced by DHA and EPA in the Pgp-overexpressing Caco-2 cells treated with paclitaxel [59]. DHA and EPA fully restored both the direct cytotoxicity and the “indirect” pro-immunogenic toxicity of doxorubicin, i.e.…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, it has been found that ω-3 PUFAs dietary deficiency might increase vulnerability to LPS-induced spatial memory impairment (Delpech et al, 2015). Furthermore, PUFAs may affect basal and stimulated production of serotonin (Kodas et al, 2004), regulate transport of antidepressants through BBB (Kuan et al, 2011) and increase the production of BDNF (Rao et al, 2007;Vetrivel et al, 2012). In turn, the effects of PUFAs on oxidative stress remain the matter of dispute regarding safety issues since pro-oxidative effects have been also reported (Di Nunzio et al, 2016).…”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%
“…Epidemiological studies showed that increased consumption of fish oil or LC n-3 PUFA is inversely correlated with CRC incidence [11, 12]. Studies have shown that LC n-3 PUFA have growth-inhibitory and pro-apoptotic effects on colon cancer cells such as HT-29, HCT-116, SW-480 and Caco-2 [1315]. Animal studies showed that fish oil supplementation reduced the number and size of polyps and suppressed the growth of cancer xenografts in nude mice [1620].…”
Section: Introductionmentioning
confidence: 99%